Network segregation is associated with processing speed in the cognitively healthy oldest-old - Sara A Nolin; Mary E Faulkner; Paul Stewart; Leland L Fleming; Stacy Merritt; Roxanne F Rezaei; Pradyumna K Bharadwaj; Mary Kate Franchetti; David A Raichlen; Cortney J Jessup; Lloyd Edwards; G Alex Hishaw; et al. (eLife)
The brain is organized into systems and networks of interacting components. The functional connections among these components give insight into the brain’s organization and may underlie some cognitive effects of aging. Examining the relationship between individual differences in brain organization and cognitive function in older adults who have reached oldest-old ages with healthy cognition can help us understand how these networks support healthy cognitive aging. We investigated functional network segregation in 146 cognitively healthy participants aged 85+ in the McKnight Brain Aging Registry (MBAR). We found that the segregation of the association system and the individual networks within the association system (the fronto-parietal network , cingulo-opercular network, and default mode network), has strong associations with overall cognition and processing speed. We also provide a healthy oldest-old (85+) cortical parcellation that can be used in future work in this age group. This study shows that network segregation of the oldest-old brain is closely linked to cognitive performance. This work adds to the growing body of knowledge about differentiation in the aged brain by demonstrating that cognitive ability is associated with differentiated functional networks in very old individuals representing successful cognitive aging.